Zimbabwean Science Studentsâ€™ Perceptions of Their Classroom Learning Environments and Attitude Towards Science - Shadreck, Mandina (Richtmann Publishing, 2012)
The purpose of the present study was to examine Zimbabwean junior secondary school studentsâ€™ perceptions of theirclassroom environment in science and to investigate relationships between these perceptions and studentsâ€™ attitudes towardscience. The study also aimed to investigate differences in studentsâ€™ attitudes toward science by gender, school location. Datawere collected from 1728 Zimbabwean junior secondary school science students in 10 Kwekwe district schools. Data werecollected with an adapted and modified version of the â€œWhat is Happening in This Classroomâ€ (WIHIC) instrument and the â€œTestof Science Related Attitudesâ€ (TOSRA). The study confirmed that the Zimbabwean version of the modified WIHIC is a valid andreliable instrument for measuring the classroom learning environment in the Zimbabwean educational context. Significantdifferences between studentsâ€™ perceptions of the actual and preferred learning environment were shown to exist with studentstending to prefer a more favorable classroom learning environment than the one which they actually are experiencing. Femalestudents generally hold more positive perceptions of the learning environments than their male counterparts. The findings alsorevealed that studentâ€™ perceptions of the classroom learning environment depending on the schoolsâ€™ locality, with students inrural schools holding less favorable perceptions than students in urban schools for all seven WIHIC scales. Correlation andregression analyses revealed that studentsâ€™ perceptions of their learning environment in science were significantly associatedwith their attitudes.